Low speed impact behaviour of adhesively bonded foam-core sandwich T-joints. Issue 3 (1st February 2019) - Caliskan, Umut; Apalak, M. Kemal
Abstract: This paper investigates the effects of foam core density and aluminum skin plates on the low speed impact behaviour of adhesively bonded sandwich T-joints having a PVC foam core and aluminum face-sheets. The dynamic response of adhesively bonded sandwich T-joints was analyzed by the explicit finite element method. Two different material models were implemented to the foam core material: a hyperelastic model and a crushable foam material with ductile damage whereas the aluminum face-sheets were modelled as an elasto-plastic material. The cohesive response of adhesive interfaces was included using three dimensional cohesive element based on cohesive zone model. Adhesively bonded sandwich T-joint specimens were manufactured and tested to validate the numerical model. A very good agreement between the experimental and FE results were achieved. The density of the foam core material of adhesively bonded sandwich T-joint played important role on the joint failure mechanism. The joint having a stiffer foam core experienced more damage in both stiffener panel and adhesive layers.